METODE PENERAPAN MODEL PEMBELAJARAN PROBLEM BASED LEARNIG (PBL) - Rahmadani Rahmadani (UIN AR-RANIRY, 2019)
This study aims to determine whether the application of the Problem Based Learning (PBL) learning model can improve students' critical thinking skills and student learning outcomes in the environmental pollution material in class X SMA Negeri 1 Darussalam Aceh Besar. The research was conducted in class X of SMA 1 Darusalam Aceh Besar of 20 students. This research was carried out of 2 cycles. Student learning outcomes data are obtained by giving a test (evaluation) in the form of a description of environmental pollution material. The research results were analyzed by descriptive analysis techniques and percentages. The results of observations of students' critical thinking abilities which showed an increase from cycle I to cycle II which was 59.75% in cycle I to 75.25% in cycle II. And student learning outcomes also increased from 70% in the first cycle to 85% in the second cycle. Based on the results of the research, it can be concluded that the application of Problem Based Learning (PBL) learning models can improve critical thinking skills and student learning outcomes.